A computational and experimental study on aerodynamics of motor-driven propellers using thrust stand and rotating cup anemometer. (7th January 2022) - Siddiqi, Zaid; Lee, Jin Wook
The aims of this study are: 1) develop a cost-effective experimental set up that incorporates a commercially available thrust-stand and rotating cup anemometer; 2) analyse rotor performance at rotational speeds ranging from 6, 000 PRM to 14, 000 RPM; 3) use the multiple reference frame (MRF) approach to develop computational fluid dynamics (CFD) simulations that provide a good agreement with experimental results; 4) to assess the efficacy of using a rotating cup anemometer to measure propeller downwash velocity. A 6-inch propeller is paired with a 2, 600 KV motor. Overall rotor efficiency peaks near 7, 200 RPM and beyond 9, 300 RPM; it declines rapidly as the mechanical and electrical power output increases. To assess the thrust and downwash velocity, two turbulence models are used in steady state: k-∈ realisable and the k-ω SST . The k-ω SST shows good overall agreements for thrust, while the k-∈ realisable provides a more accurate modelling of the downwash velocity. Based on the CFD results, the rotating cup anemometer is found to be unsuitable for measuring propeller downwash velocities.